Richard Hooker and the Vision of God Exploring the Origins of 'Anglicanism'. - Miller, Charles (James Clarke and Co, 2013)
Finally filling the gap between specialist volumes and 'companion texts', Charles Miller's rigorous and well written exploration of the works and theology of Richard Hooker is a comprehensive and critical testament to one of the most important founders of Anglican thoughtMiller introduces the main theological topics in Hooker's writings and identifies his distinctive contribution to the emergence of Anglicanism via discussion of such themes as Hooker's conception of God, of Mankind and of the place of Scripture in the Church. These discussions are deeply founded on Hooker's own works and Mille.
Why study Richard Hooker? -- 'That glorious beam of the English Church': the man and his world -- 'The weight of this requireth largenesse': the big picture -- 'That light which none can approach unto': God -- 'To shew beneficence and grace': creation -- 'The noblest creature in the world': humankind -- 'A way mystical and supernatural': scripture -- 'Life and light eternal': Jesus Christ -- 'Generative force and virtue': the Holy Spirit and grace -- 'The sovereign observances of God's grace': worship and sacraments -- 'The signs of God's love': baptism and the Eucharist -- 'A holy rule of doing well': faith and works -- 'The science of things divine': theology and doctrine -- 'Our good: our sovereign good': moral theology -- 'Our desire to behold God': spiritual theology -- 'That visible mystical body': ecclesiology -- 'The public ministry of holy things': ministry -- 'The laws by which we live': political theology.
Print version record.
Includes bibliographical references (pages 335-342) and indexes.
Master record variable field(s) change: 072
Keywords: Hooker, Richard, -- 1553 or 1554-1600.; Hooker, Richard, -- 1553 or 1554-1600.; Theologians -- England; Anglicans -- England; Theology, Doctrinal; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; Anglicans; Theologians; Theology, Doctrinal; England; RELIGION / Christian Theology / General; Electronic books